Why Does Discrimination Against Indigenous Beliefs Persist in Indonesia? - Nurwansyah, Agus; Hidayat, Taufiq (Contemporary Society and Politics Journal, 2024)
The number of adherents of traditional beliefs in Indonesia is approximately 12 million, spread across 27 provinces. However, despite this significant number, they have not yet been recognized by the state as equal to formal religions in the religion column on their Identity Cards (KTP). This study employs a descriptive-qualitative method based on a critical paradigm, using Antonio Gramsci’s theory of hegemony as its analytical framework. The findings reveal that state hegemony began with the consensus to label traditional beliefs as "faith streams" through the Ministry of Religion in 1961. This was followed by political, ideological, and leadership hegemony through various discriminatory laws and regulations targeting those identified as adherents of traditional beliefs. The Constitutional Court's decision to allow the inclusion of “Belief in the Almighty God” in the religion column of the KTP represents a form of resistance to hegemony through intellectual movements.